Effect of Infill Wall Opening Ratio on the Mechanical Characteristics of Reinforced Concrete Frames - Pham, Phu-Anh-Huy; Le, Cao-Vinh; Nguyen, Van-Tien (Civil Engineering Journal, 2025)
This study investigated the influence of infill wall (IW) opening ratios on the mechanical performance of reinforced concrete (RC) frames using a novel numerical model. The proposed model incorporated stiffness degradation and a nonlinear "Gap Element" to simulate the interaction between RC frames and IWs under seismic loading. A 3D finite element model was developed in SAP2000 and calibrated using validated experimental data. Parameters such as IW thickness, opening ratio (0–100%), and opening position (symmetric, asymmetric, corner) were systematically varied to assess their effects on lateral displacement , fundamental period , shear force , and bending moment . The results indicated that increasing the opening ratio significantly reduces frame stiffness, especially beyond 40%, and leads to substantial increases in displacement. Corner openings were found to have the most detrimental impact, while thicker walls (≥220mm) can partially mitigate stiffness loss. However, at ratios above 60%, even thick IWs failed to preserve structural performance. Based on these findings, a limit of 40% opening ratio was recommended for design purposes, and reinforcement was advised for higher ratios. The study provides a practical framework for optimizing the seismic and structural design of RC frames with openings in IWs, contributing new thresholds and modeling strategies for improved performance.